2020
DOI: 10.1371/journal.pone.0230170
|View full text |Cite
|
Sign up to set email alerts
|

The rodent vaginal microbiome across the estrous cycle and the effect of genital nerve electrical stimulation

Abstract: Treatment options are limited for the approximately 40% of postmenopausal women worldwide who suffer from female sexual dysfunction (FSD). Neural stimulation has shown potential as a treatment for genital arousal FSD, however the mechanisms for its improvement are unknown. One potential cause of some cases of genital arousal FSD are changes to the composition of the vaginal microbiota, which is associated with vulvovaginal atrophy. The primary hypothesis of this study was that neural stimulation may induce hea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…discovered that, compared with control rats, rats receiving twice-weekly 30-min sessions of cutaneous ES targeting the genital branch of the pudendal nerve experienced less change in the composition of their vaginal microbiota. This finding suggested that ES might stabilize the vaginal microbiota, which is similar to our conclusion and point ( Levy et al., 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…discovered that, compared with control rats, rats receiving twice-weekly 30-min sessions of cutaneous ES targeting the genital branch of the pudendal nerve experienced less change in the composition of their vaginal microbiota. This finding suggested that ES might stabilize the vaginal microbiota, which is similar to our conclusion and point ( Levy et al., 2020 ).…”
Section: Discussionsupporting
confidence: 92%
“…Ketamine-xylazine anesthesia has also resulted in delayed recovery and possible hypoxia [36]. Animal death secondary to anesthesia decreased the sample size and strength of this study and may have contributed to variability in group measures, although previous studies [26] had as little as 5 animals per experimental group. In this study, many comparisons between OVX stim and control groups were close to significance (p = 0.05 -0.1), and more definitive conclusions may have been drawn without animal loss decreasing sample size.…”
Section: Discussionmentioning
confidence: 97%
“…The average relative abundance of lactobacilli in nonhuman mammalian species was only approximately 1.1% compared to the nearly 70% dominance found in women (43). One study reported that the rat vaginal microbiome is dominated primarily by Proteobacteria, Firmicutes, and Actinobacteria phyla (48). Analyses in the mouse demonstrated that Staphylococcus and Enterococcus genera predominate and that cycling hormones do not significantly disrupt established microbial consortia (49).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, again, vaginal pH was not specifically monitored. Disparate results between studies may very well be accounted for by resident vaginal microbiota, which is likely to be highly variable between animal suppliers, animal vivariums, and individual rodents (48,49). Perhaps microbiome composition using conventionalized mice and not pH per se should be controlled for improved model consistency.…”
Section: Discussionmentioning
confidence: 99%